The lncRNA SENCR knockdown alleviates vascular calcification via miR-4731-5p by suppressing endoplasmic reticulum stress - Yongpan Huang; Wei Zhan; Chong Song; Meihua Tan; Li Wu; Sina Wu (PLoS ONE, 2025)
Background Accumulation of calcium phosphate crystals is associated with vascular calcification (VC); however, the mechanism that promotes VC remains unclear. Accumulating evidence indicates that smooth muscle and endothelial cell-enriched migration/differentiation-associated lncRNA (SENCR) exerts a critical role in VC. This work focuses on the molecules involved in β-glycerophosphate-induced osteogenic differentiation of vascular smooth muscle cells (VSMCs) through SENCR epigenetic modification of Runx2 in an endoplasmic reticulum stress (ERS)-dependent manner. Methods We cultured VSMCs to explore the relationship among β-glycerophosphate, SENCR, and VC and also investigate the function of SENCR in β-glycerophosphate-induced osteogenic differentiation and VC in vitro. Results Our findings indicate that β-glycerophosphate enhanced SENCR, MSH homeobox 2, Runx2, ERS-related markers, alkaline phosphatase activity, and cellular calcium deposition and suppressed the expression of α-SMA, SM 22α, and miR-4731-5p. SENCR silencing increased miR-4731-5p expression, which subsequently inhibited β-glycerophosphate-associated endoplasmic reticulum stress at the post-transcriptional level. Critically, the facts that direct interplay between SENCR and miR-4731-5p, and the downregulation of miR-4731-5p efficiently reversed the suppression of ERS-induced by SENCR silencing were observed. Collectively, the present study clarifies a novel mechanism by which downregulation of SRNRC contributes to the ERS-dependent osteogenic differentiation of VSMCs and VC by sponging miR-4731-5p. This study demonstrates that SENCR/miR-4731-5p axis is involved in β-glycerophosphate-mediated VC in vitro.